PENGARUH JENIS UMPAN TERHADAP HASIL TANGKAPAN IKAN SIDAT (Anguilla spp.) DI SUNGAI TANJUNG AGUNG BENGKULU - Zamdial Zamdial; Ali Muqsit; Nofan A. Sholih (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2025)
Bengkulu Province, which is located on the West Coast of Samudera Island, is known to have a coastline of ± 525 km, and is directly connected to the Indian Ocean. There are several large rivers that flow to the coast of Bengkulu Province. Fish resources in the waters of Bengkulu Province are quite potential, both in terms of number and type of fish. One type of fish that is currently receiving attention for use and development is the eel (Anguilla spp.). Bengkulu Province, which ranks second in terms of eel production in Indonesia, with a contribution of 16.1% in 2018. This research aims to analyze the effect of various types of bait on catches of eels (Anguilla spp.) in the Tanjung Agung River, Sungai Serut District, Bengkulu City. This research was carried out using experimental methods. There were 3 types of bait used in this research, namely worms, shrimp and snails. This research used a Completely Randomized Design (CRD) and data analysis used the Kruskal-Wallis Test. Only one species of eel was caught, namely Anguilla bicolor. Apart from eels, other types of fish were also caught, namely tilapia (Oreochromis niloticus), betok fish (Anabas testudineus) and catfish (Clarias batrachus). The difference between three types of bait has no effect on the catch of eels (Anguilla spp.) using hand lines in the Tanjung Agung River, Bengkulu City.